Hubungan Strategi Koping Dengan Stres Warga Binaan Pemasyarakatan Di Rumah Tahanan Negara Kelas IIb Kupang - Kurniawaty, Yuni; Sose, Fransiskus Dede Kusumawan (Jurnal Keperawatan Muhammadiyah, 2021)
Objective:   The aim of this study was to analyze the relationship between coping strategies and stress among inmates at Kupang Class IIB State Detention Center.Methods:   This type of research correlates with cross-cutting design. The population of this study consisted of inmates from Kupang Class IIB State Detention Center with a total of 246 people. The sampling method is based on reasoned use. The sample for this study was 150 people. The independent variable is the adaptation strategy using the BriefCOPE measuring instrument. The stress dependent variable is the Perceived Stress Scale (PSS-10). Results:   Pearson's correlation test with a p value = 0.001 <0.05 means that there is a significant relationship between coping strategies and stress of inmates at Kupang Class IIB State Detention Center. The correlation coefficient (r) = - 333 with a low correlation value, the nature of the negative relationship means that the higher the coping strategy, the lower the inmate stress level.Conclusion:  The breadth of significance of a person's ability to use coping strategies to cope with stress requires a better understanding of the role of personality traits and their relationship to coping strategies that enable psychological interventions. more targeted and effective which in turn will increase inmates' ability to cope with stress.